Analisis Faktor-faktor Produksi Usahatani Tebu di Desa Banyuputih Kecamatan Banyuputih Kabupaten Situbondo - Mayangsari, Andina (Universitas Galuh, 2024)
The aim of this research is to identify factors that influence production in the sugar cane farming sector and evaluate the scale of production in sugar cane farming in Banyuputih Village, Banyuputih District, Situbondo Regency. The data used involves primary information obtained directly from farmers, including variables such as name, age, education level, land area, amount of seed used, amount of fertilizer used, and number and type of workforce. Secondary data was also obtained from various agencies and institutions, including the Central Statistics Agency (BPS). The research was carried out on all sugar cane farmers in Banyuputih Village, Banyuputih District, by selecting 30 respondents as samples using non-probability sampling with a purposive sampling technique. The data analysis method applied is the Cobb-Douglas production function model using SPSS software. The research results show that, based on the Cobb-Douglas production function analysis, it can be concluded that sugar cane farming in Banyuputih Village, Banyuputih District, Situbondo Regency, is significantly influenced by the use of seeds, urea fertilizer, phonska fertilizer, and labor. Simultaneously, all observed variables have a significant influence on sugarcane production. Furthermore, the scale of production businesses in sugar cane farming in Banyuputih Village, Banyuputih District, Situbondo Regency, was found to be in a condition of Increasing Return to Scale.